2021
DOI: 10.1039/d1sc02295d
|View full text |Cite
|
Sign up to set email alerts
|

Influence of stereochemistry on the activity of rapadocin, an isoform-specific inhibitor of the nucleoside transporter ENT1

Abstract: Rapadocin is a novel rapamycin-inspired polyketide-tetrapeptide hybrid macrocycle that possesses highly potent and isoform-specific inhibitory activity against human equilibrative nucleoside transporter 1 (hENT1). Rapadocin contains an epimerizable chiral center in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Stereochemistry is an important factor in drug design because changes affect biological chemistry. , In rapadocins, differences in stereochemistry induced 200-fold changes in IC 50 (Figure S2). Furthermore, among diaminosuberic amino acid-derived compounds with two stereocenters yielding four stereoisomers, only a single stereoisomer among the four exhibited high inhibitory activity in the micromolar range against the amino acid transporter . Therefore, the diversification of stereochemistry is one of the important strategies for nature to generate natural products with a wide range of biological functions.…”
Section: Introductionmentioning
confidence: 99%
“…Stereochemistry is an important factor in drug design because changes affect biological chemistry. , In rapadocins, differences in stereochemistry induced 200-fold changes in IC 50 (Figure S2). Furthermore, among diaminosuberic amino acid-derived compounds with two stereocenters yielding four stereoisomers, only a single stereoisomer among the four exhibited high inhibitory activity in the micromolar range against the amino acid transporter . Therefore, the diversification of stereochemistry is one of the important strategies for nature to generate natural products with a wide range of biological functions.…”
Section: Introductionmentioning
confidence: 99%
“…Solid-phase synthesis is a powerful tool in peptide synthesis, [7][8][9] and several destruxin analogues have been synthesized via this method. 10,11 It is well known that the macrocyclization step is the key step in cyclodepsipeptide synthesis, especially in the macrolactamization of N-alkylated amino acids (N-methyl amino acids or proline) 12 and in macrolactonization. 13,14 It has been reported that the macrolactamization of N-alkylated amino acids has the potential to introduce cis-amide bonds into peptides and results in a turninducing isomer, 15,16 and the lower nucleophilicity of N-alkylated amine and hydroxy also leads to a lower yield of macrocyclization compared to the primary amine case.…”
Section: Introductionmentioning
confidence: 99%